Analysis of Faults in the Mechanical Part of Railway Weight Checking Wagons - Nodir Botir ugli Adilov; Nodir Botir ugli Adilov (Genius Journals, 2022)
In this article, the problem is relevant, such as extending the service life of 640-VPV weighing wagons operated on the territory of the Republic of Uzbekistan. The analysis of the technical condition of the weighing wagon metal structures revealed defects that could affect their service life
Keywords: Railway; six-axle wagon; pivot beam; longitudinal beam